PEMUJAAN PALINGGIH BE JULIT DI DESA BESTALA KECAMATAN SERIRIT KABUPATEN BULELENG - Putu Subawa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Hindus in worshiping God (Ida Sang Hyang Widhi Wasa) with all its great, almighty, abstract manifestations can not be reached by human reason, so that Hindus in worshiping him by using symbols / embodiments. As with the embodiment of ratu ayu (rangda) and barong, various types of statues, statues. The worship of Palinggih Be Julit as a function of relegi is a medium to meet the longing of the religious sense of society. As a function of protection, the presence of Palinggih Be Julit is not only a tool of concentration for society. He also has the power capable of giving people a sense of comfort for penyungsungnya, as well as a function of conservation, where with the worbling palinggih Be Julit community in the village of Bestala Seririt district Buleleng district is a form of citizen participation to always preserve Be Julit (Ikan Sidat) So that it does not quickly experience extinction due to excessive hunting. : Worship, Palinggih Be Julit, Buleleng